HOW DO DIFFERENT DEBT LEVELS INFLUENCE THE FINANCIAL PERFORMANCE OF FMCG COMPANIES IN INDIA? - Priyanka; Singh, Rajbir (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study examines the impact of capital structure on the financial performance of Fast-Moving Consumer Goods (FMCG) companies listed on the Bombay Stock Exchange (BSE) from 2011 to 2021. It focuses on how varying levels of short-term, long-term, and total debt influence key financial metrics such as Return on Assets (ROA), Return on Equity (ROE), Earnings Per Share (EPS), and Tobin’s Q. Using regression models with panel data, the research evaluates the relationship between debt ratios and financial performance, utilizing both fixed and random effects models. The findings reveal that higher levels of debt, especially long-term debt, negatively impact financial performance. Short-term debt is more commonly used in the FMCG sector, but overall, debt tends to reduce profitability and shareholder value. Notably, Earnings Per Share (EPS) had the highest average among the performance indicators, though all debt ratios demonstrated significant negative correlations with ROA, ROE, EPS, and Tobin’s Q. The study also highlights that larger and older firms are more effective at managing the negative effects of debt, performing better financially than smaller or younger firms. It recommends that FMCG companies prioritize internal funding over debt, as high debt levels can lead to financial strain. Future research could explore the impact of capital structure in other industries or include macroeconomic factors.